Spesiasi Aluminium Terlarut dan Sifat Kimia Ultisol yang Diameliorasi dengan Dolomit dan Lignit-Teraktivasi - Fahmi Arief Rahman; Budi Nugroho; Atang Sutandi; Untung Sudadi (Jurnal Ilmu Pertanian Indonesia, 2021)
Phytotoxicity of soil aluminum (Al), both directly to the plant growth as well as indirectly through the increase of soil potential acidity, is closely related to the occurrence of various soil soluble-Al species. Amongst them, Al3+ and monomeric-Al species are the primary causes of Al phytotoxicity in soils with high Al content. This study was aimed to evaluate the effects of soil amelioration with dolomite and base-activated lignite (BAL) on changes in soluble-Al species and other soil chemical properties, and vegetative growth of soybean (Glycine max Merr) on Ultisol of Jasinga (Al-dd 16,03 cmol(+)/kg). A green house experiment was conducted by applying a Completely Randomized Design with dolomite and BAL amelioration as the treatments, each with three levels of repectively 0, 1, 1,5 x exchangeable-Al and 0, 2,5, 5 tons BAL ha-1, and three replications. The ameliorants were incubated at field capacity of soil moisture content for one week before planting soybean for one month. Soil soluble-Al speciation was carried out using colorimetric aluminon method to determine concentrations of total soluble-Al, monomeric-Al, and polymeric-Al species. Monomeric-Al were further speciated into inorganic monomeric-Al and organic monomeric-Al species. The results revealed that only dolomite amelioration that significantly increased soil pH-H2O, pH-KCl, Ca- dd, Na-dd, and decreased exchangeable-Al concentration, except for those of all soluble-Al species that only showed a decreasing trend. Soil exchangeable-Al that was negatively and significantly correlated with soybean measure parameters were plant height, root length, total roots and shoots wet and dry weights, as well as Ca concentration. These results indicated that soil Al phytotoxicity evaluation could be relied on the result of routine analysis on soil exchangeable-Al concentration. Keywords: exchangeable-Al, inorganic monomeric-Al, organic monomeric-Al, polymeric-Al